Sistem Monitoring Debit Air Berbasis Internet of Things pada Saluran Air - Sutikno, Tole; Susanto, Defri Rahmad; Purnama, Hendril Satrian (Majalah Ilmiah Teknologi Elektro, 2023)
Manual measurement and recording of water debits has many drawbacks, including inaccuracies, time inefficiencies and requires a lot of human effort. Along with technological developments, the Internet of Things (IoT) is the right option to reduce human interaction with hardware in terms of continuous monitoring. This study aims to design a prototype of a water discharge monitoring system with precise accuracy and efficient use of electrical energy. The water discharge monitoring device system is designed based on IoT with NodeMCU as the main processor, while the water flow sensor is used as a transducer in charge of collecting data. Furthermore, the data collected by the hardware will be sent to the server with the IoT protocol via Blynk application. The results of the study show that the designed system works well, able to transmit data via IoT remotely, and has relatively high accuracy.